2013
DOI: 10.1186/1741-7015-11-205
|View full text |Cite
|
Sign up to set email alerts
|

Myalgic encephalomyelitis/chronic fatigue syndrome and encephalomyelitis disseminata/multiple sclerosis show remarkable levels of similarity in phenomenology and neuroimmune characteristics

Abstract: Background‘Encephalomyelitis disseminata’ (multiple sclerosis) and myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) are both classified as diseases of the central nervous system by the World Health Organization. This review aims to compare the phenomenological and neuroimmune characteristics of MS with those of ME/CFS.DiscussionThere are remarkable phenomenological and neuroimmune overlaps between both disorders. Patients with ME/CFS and MS both experience severe levels of disabling fatigue and a wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
153
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 139 publications
(160 citation statements)
references
References 312 publications
(322 reference statements)
7
153
0
Order By: Relevance
“…Th1-like cytokines, such as IL-2, IL-12, and interferon (IFN)-γ, are often increased in active disease states [8][9][10][11], whereas Th2-like cytokines, including IL-4 and IL-10, may be increased during remission [15][16][17][18]. Nevertheless, concomitant increases in the expression of Th1-and Th2-like cytokines may be present during an acute attack [5,19]. Recently, we observed that TNF-β NcoI polymorphism is significantly associated with MS, i.e., the TNFB2/B2 genotype is associated with MS and with increased TNF-α levels [20].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Th1-like cytokines, such as IL-2, IL-12, and interferon (IFN)-γ, are often increased in active disease states [8][9][10][11], whereas Th2-like cytokines, including IL-4 and IL-10, may be increased during remission [15][16][17][18]. Nevertheless, concomitant increases in the expression of Th1-and Th2-like cytokines may be present during an acute attack [5,19]. Recently, we observed that TNF-β NcoI polymorphism is significantly associated with MS, i.e., the TNFB2/B2 genotype is associated with MS and with increased TNF-α levels [20].…”
Section: Introductionmentioning
confidence: 95%
“…Increased levels of IO&NS biomarkers are observed in the brain, cerebrospinal fluid (CSF), and blood of MS patients [4,5]. For example, increased levels of the proinflammatory cytokines, such as interleukin (IL)-1β, IL-6, and tumor necrosis factor-α (TNF-α), are observed in the plasma or CSF of patients with MS [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 96%
“…Interestingly, serum IgM levels to these anchorage molecules were significantly higher in patients afforded a diagnosis of chronic fatigue syndrome than they were in patients with major depression disorder suggesting increased levels of ROS and RNS [267]. Numerous authors have reported a range of other antibodies towards different lipid species whose origin is largely difficult to determine, although it is highly likely that reported antiganglioside antibodies were directed against gangliosides shed from disrupted lipid rafts [7].…”
Section: Lipid Rafts Mlrs and N-3 Pufas In Chronic Fatigue Syndromementioning
confidence: 96%
“…Oxidative and nitrosative stress (O&NS) and chronic systemic inflammation are interrelated factors implicated in the pathophysiology of Alzheimer's disease [1,2], Parkinson's disease [3,4], multiple sclerosis [5,6], chronic fatigue syndrome [7,8], schizophrenia [9,10] and major depression [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Many such patients are afforded the exclusionary, non-specific, diagnosis of chronic fatigue syndrome (CFS), according to a plethora of different selection criteria [3], if rudimentary testing does not reveal the cause of their symptoms. Sophisticated tests, however, often reveal profound immunological abnormalities in such patients and evidence of active pathogen activity [4,5]. A study of 375 patients with apparently idiopathic disabling fatigue revealed pathological stimulation of lymphocytes together with abnormally elevated and distributed pattern of CD4 + , CD8 + , and CD19 + leucocytes in 53 % of patients and depleted levels of IgG 3 in 59 % of the study population.…”
Section: Introductionmentioning
confidence: 99%